PEMILIHAN ALTERNATIF ARMADA ANGKUTAN PENDISTRIBUSIAN BAN PADA PT DERMAGA SUKSES JAYA ABADI - Eka Yudhyani, Meivi Riva Kawet, LCA Robin Jonathan2, (EKONOMIA, 2015)
Meivi Riva Kawet, 2015, Economy Faculty of 17 Agustus 1945 University of Samarinda, Alternative Choosing for Transportation Tires Distribution in PT Dermaga Sukses Jaya Abadi Samarinda (under guidance Mr Jonathan and Mrs Yudhyani)The purpose of this research is to find out and analyzed the decision of distributing tires between buying new transportation the type is Toyota Dyna PS 130 or lease the expedition.Depend on the purpose of this research is Which one more profitable, buy new transportationÂ or lease the expedition?Based on the problem, hypothesis submitted is: â€œ Buying new transportation is more profitable than lease the expedition.â€Analysis tools which use in this research is Net Present Value Method, that using the discount factor from the capital cost of the company.Â Then compare Present Value from cash outflow between buying new armada Toyota Dyna PS 130 or lease the expedition.The result of this research is Present Value from cash outflow of Toyota Dyna PS 130 is Rp 1.726.654.457,- but if lease the expedition is Rp 2.012.270.400,-.Â The gain is Rp 285.615.943, so the company will more profitable if buy the new transportation because can saving cost Rp 285.615.943,- or 14,19%.Â Based on the result, the hypothesis is accepted, because buying the new transportation more profitable than lease the expedition.Â